2013
DOI: 10.1002/14651858.cd009416.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for treating pain and disability in adults with complex regional pain syndrome- an overview of systematic reviews

Abstract: Interventions for treating pain and disability in adults with complex regional pain syndrome-an overview of systematic reviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 160 publications
(92 citation statements)
references
References 215 publications
1
75
0
4
Order By: Relevance
“…Furthermore, the clinical effects do not appear to be significant to change either syndrome development or quality of life. Even multiple-session of rTMS did not consistently reveal to be effective [21,31,32]. In agreement to this, it has been reported that CRPS pain improvement only occurs during rTMS sessions [31,32].…”
Section: Repetitive Transcranial Magnetic Stimulation (Rtms)mentioning
confidence: 82%
See 4 more Smart Citations
“…Furthermore, the clinical effects do not appear to be significant to change either syndrome development or quality of life. Even multiple-session of rTMS did not consistently reveal to be effective [21,31,32]. In agreement to this, it has been reported that CRPS pain improvement only occurs during rTMS sessions [31,32].…”
Section: Repetitive Transcranial Magnetic Stimulation (Rtms)mentioning
confidence: 82%
“…Furthermore, controlled trials have never succeeded in proving the effectiveness of either guanethidine intravenous infusion or surgical sympathectomy, which sometimes are associated to high rates of adverse events [21].…”
Section: Journal Of Neurology and Neuroscience Issn 2171-6625mentioning
confidence: 99%
See 3 more Smart Citations